Pengaruh Kecerdasan Emosional terhadap Kualitas Penggembalaan di Gereja Suara Kebenaran Injil Se- Sumatera Utara - Rinto Francius Sirait; Merlin Santinus (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
Pastoral care within the Voice of Truth Gospel Church throughout North Sumatra has experienced a decline in quality in fostering the maturity of faith and the spiritual life of the congregation. The purpose of this study is to determine the extent to which emotional intelligence influences the quality of pastoral care within the Voice of Truth Gospel Church throughout North Sumatra. This study uses a quantitative approach. The data obtained were analyzed using simple linear regression techniques. This study proves that: Based on data reduction, it is known that the emotional intelligence of pastors, administrators, and servants of the Voice of Truth Gospel Church in the North Sumatra region is in the high category; Based on the results of data reduction, it is also known that the majority of respondents assess that pastoral care within the Voice of Truth Gospel Church throughout North Sumatra has been running quite effectively; Emotional Intelligence has a positive and significant effect on the variable of Pastoral Care Quality. This can be seen from the calculated t (8.857) > t table (1.65437) and Sig. (0.000) < 0.05, and based on the results of the coefficient of determination test, it is known that the Quality of Herding is influenced by the Emotional Intelligence variable with a value of 61.2% and the remaining 39.8% is influenced by other variables outside this study.